Book Review: The Imaginary Domain, by Drucilla Cornell - Dougherty, Terence (Columbia Journal of Gender and Law, 1996)
In an overall sense, feminist legal theory can be seen as being comprised of two theoretical models that are seemingly irreconcilable. In their appeal to equality through legal reform, many legal feminists passionately identify with either formal or substantive equality. Initially, the feminist appeal to equality involved the claim that men and women are essentially the same. This is known as formal equality. This appeal to likeness between men and women as the basis for a feminist model for equality is primarily due to two things: 1) to a commitment to the idea that men and women have similar potentialities, and 2) to the nature of progressive legal reform in this country that attempts to equalize members of society as each deserving of the same set of rights. All people in a democratic society are created equal and thus all can expect the law to ensure that they be equal. For discrimination on the basis of gender to have legal meaning within this model, a woman claiming gender discrimination must define that characteristic of her gender that is being affected by the discrmination via a comparison with men. And in order for there to be a basis for this comparison with men, the characteristic must be universal to women. Otherwise, the comparison would only be made within the class of women-an intraclass claim.